Central Circadian Control of Female Reproductive Function - Miller, Brooke H.; Takahashi, Joseph S. (Frontiers in Endocrinology, 2014)
Over the past two decades, it has become clear just how much of our physiology is under the control of the suprachiasmatic nucleus (SCN) and the cell-intrinsic molecular clock that ticks with a periodicity of approximately 24 hours. The SCN prepares our digestive system for meals, our adrenal axis for the stress of waking up in the morning, and the genes expressed in our muscles when we prepare to exercise, Long before molecular studies of genes such as Clock, Bmal1, and the Per homologs were possible, it was obvious that female reproductive function was under strict circadian control at every level of the hypothalamic-pituitary-gonadal (HPG) axis, and in the establishment and successful maintenance of pregnancy. This review highlights our current understanding of the role that the SCN plays in regulating female reproductive physiology, with a special emphasis on the advances made possible through the use of circadian mutant mice.